Identification of a novel nemaline myopathy‐Causing mutation in the troponin T1 (TNNT1) gene: A case outside of the old order amish. Issue 5 (17th February 2015) - Marra, Jonathan D.; Engelstad, Kristin E.; Ankala, Arunkanth; Tanji, Kurenai; Dastgir, Jahannaz; De Vivo, Darryl C.; Coffee, Bradford; Chiriboga, Claudia A.
ABSTRACT: Introduction : Nemaline myopathy (NM) is a congenital neuromuscular disorder often characterized by hypotonia, facial weakness, skeletal muscle weakness, and the presence of rods on muscle biopsy. A rare form of nemaline myopathy known as Amish Nemaline Myopathy has only been seen in a genetically isolated cohort of Old Order Amish patients who may additionally present with tremors in the first 2–3 months of life. Methods : We describe an Hispanic male diagnosed with nemaline myopathy histopathologically and subsequently confirmed by next generation gene sequencing. Results : Direct sequencing revealed that he is homozygous for a pathogenic nonsense variant c.323C>G (p.S108X) in exon 9 of the TNNT1 gene. Conclusions : This report describes a novel pathogenic variant in the TNNT1 gene and represents a nemaline myopathy‐causing variant in the TNNT1 gene outside of the Old Order Amish and Dutch ancestry. Muscle Nerve 51 :767–772, 2015